Ribosome assembly during recovery of heat-injured Staphylococcus aureus cells. - Flowers, R S (1980)
The process of ribosome formation during repair of sublethal heat injury was examined in Staphylococcus aureus. Sublethal heating of this organism results in the degradation of the 30S ribosomal subunit and alteration of the 50S subunit. Cells recovering from sublethal injury were examined for changes with time in the sedimentation and electrophoretic properties of ribonucleoprotein particles and ribonucleic acid, respectively. When cells were allowed to recover in [3H]uridine, the label could be followed into ribonucleic acid species that coelectrophoresed with 23S and 16S ribonucleic acid. Three ribonucleoprotein particles (49S, 36S, and 30S) were isolated from repairing cells by sedimentation through sucrose gradients. Polyacrylamide gel electrophoresis showed that the 49S particle contained 23S ribonucleic acid, the 36S particle contained both 23S ribonucleic acid and 16S precursor and mature ribonucleic acid, and the 30S particle contained 16S and precursor 16S ribonucleic acid. Particles with similar sedimentation properties were found in unheated cells.